Quality of Wild Passion Fruit at Different Ripening Stages Under Irrigated and Rainfed Cultivation Systems - Giuliana Naiara Barros Sales; Marília Hortência Batista Silva Rodrigues; Toshik Iarley da Silva; Rodolfo Rodrigo de Almeida Lacerda; Brencarla Lima Medeiros; Larissa Felix Macedo; Thiago Jardelino Dias; Walter Esfrain Pereira; Fabio Gelape Faleiro; Ivislanne de Sousa Queiroga Lacerda; Franciscleudo Bezerra da Costa (Plants)
Passiflora cincinnata (Mast), native to the Brazilian semi-arid region, produces exotic fruits even under low water availability. However, its green coloration at ripening complicates optimal harvesting, impacting post-harvest fruit quality. Therefore, this study aimed to evaluate the influence of cultivation systems (irrigated and rainfed) and different ripening stages on the physical and post-harvest characteristics of wild passion fruit during the second production cycle. The experiment was conducted using a randomized block design in a 2 × 4 factorial scheme, corresponding to two cultivation systems (irrigated and rainfed) and four fruit ripening stages (60, 80, 100, and 120 days after anthesis—DAA), with five replications. The fruit pulps were analyzed for physicochemical characterization and bioactive compounds. The physical and chemical characteristics of wild passion fruit were influenced by ripening stages and the irrigation system. The rainfed system decreased the total fruit mass by 15.50% compared to the irrigated cultivation. Additionally, the rainfed cultivation reduced the fruit color index by 14.82% and altered the respiratory pattern, causing a linear decrease of 73.37% in the respiration rate during ripening, in contrast to the behavior observed in the irrigated system, which reached an estimated minimum rate of 33.74 mg CO2 kg−1 h−1 at 110 days after anthesis.